A framework of tools for managing software architecture knowledge - Abdullah, Rusli; Mohamed Shah, Zainab; Mohamed, Amir Mohamed Talib (Canadian Center of Science and Education, 2011)
Software architecture (SA) process consists of several activities, which involve complex knowledge intensive process. The knowledge produced and consumed during this process needs to be shared and reused among different stakeholders, and across different life-cycle phases. Therefore, software architecture knowledge needs to be managed for improving organization architecture capabilities. It is the way knowledge management (KM) plays an important role in the SA process. This paper utilized SA evaluation to analyze SA and used Architecture Tradeoff Analysis Method (ATAM) to support a disciplined architecture process. With this approach, it gives support to provide or manage the knowledge required or generated during the SA process. The effective tool support is needed and become important to capture and manage architectural knowledge (AK) consumed or generated during SA process. If not captured and managed, this critical knowledge is implicitly embedded in the architecture, become tacit knowledge which erodes as personnel on the project change. To cover these issues, this paper developed a framework of tools for managing SA knowledge. The tool prototype designing and implementing a web-based knowledge management system (KMS), which is offer a hybrid architectural KM approach.